I have, for a fixed and positive even integer $n$, the following product of summations:

$\left ( \sum_{i = n-1}^{n-1}i \right )\cdot \left ( \sum_{i = n-3}^{n-1} i \right )\cdot \left ( \sum_{i = n-5}^{n-1}i \right )\cdot ... \cdot \left (\sum_{i=5}^{n-1}i \right )\cdot \left (\sum_{i=3}^{n-1}i \right )\cdot \left (\sum_{i=1}^{n-1}i \right )$

Where there are $\frac{n}{2}$ groups of summations multiplied together.

For example, consider the case where $n=4$ :

$\left ( \sum_{i = 3}^{3}i \right )\cdot \left ( \sum_{i = 1}^{3} i \right ) = \left ( 3 \right )\left ( 1+2+3 \right ) = 18$

I have tried in vain to simplify the product. Perhaps there are identities I could make use of.

Edit : I can expand the product to clarify:

$$\left ( n-1 \right )\cdot \left [ (n-3)+(n-2)+(n-1) \right ]\cdot \left [ (n-5)+...+(n-1) \right ]\cdot ... \cdot\left [3+4+...+(n-1)\right ]\cdot \left [1+2+...+(n-1) \right ]$$

From where I can see a $(n-1)^{\frac{n}{2}}$ term, but the others are quite jumbled.

  • 1
    $\begingroup$ I don't see any particular way this is going to simplify. I would actually work out the values of each sum (they're just arithmetic progressions) - for example, the last factor is just $(n-1)n/2$ - that should make things a little simpler, once the sums are gone. $\endgroup$ – Greg Martin May 23 '13 at 18:25

Let $n=2m$. Your expression is then

$$\begin{align*} &(2m-1)\cdot\frac32(2n-4)\cdot\frac52(2n-6)\cdot\ldots\cdot\frac{n-1}2n\\\\ &\qquad=1\cdot(2m-1)\cdot3(2m-2)\cdot5(2m-3)\cdot\ldots\cdot(2m-1)m\\\\ &\qquad=\prod_{k=1}^m(2k-1)(2m-k)\\\\ &\qquad=(2m-1)!!\frac{(2m-1)!}{(m-1)!}\\\\ &\qquad=\frac{(2m)!}{2^mm!}\cdot\frac{(2m-1)!}{(m-1)!}\\\\ &\qquad=\frac{(2m)!}{2^m}\binom{2m-1}m\\\\ &\qquad=\frac{n!}{2^{n/2}}\binom{n-1}{n/2}\;. \end{align*}$$

  • $\begingroup$ This is exactly what I was looking for. Thanks a lot! $\endgroup$ – FlamingWilderbeest May 23 '13 at 20:00
  • $\begingroup$ @FlamingWilderbeest: You’re welcome! $\endgroup$ – Brian M. Scott May 23 '13 at 20:14

Note that $ \displaystyle \sum_{i=n - 2k +1}^{n-1} i = (2k - 1)(n-k) $. Let $ n = 2m $ $$ \begin{align*}\prod_{k = 1}^{\frac{n}{2}} (2k - 1)(n- k) &= \prod_{k = 1}^{m} (2k - 1) \prod_{k=1}^m (2m - k) \\ &=(2m-1)!! \frac{(2m-1)!}{(m-1)!} \end{align*}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.